THE INFLUENCE OF HEALTH EDUCATION ON HEALTHY FOOD / STICK ON THE ATTITUDES OF CHILDREN IN CHOOSE HEALTHY FOOD / HOODS ON PRIMARY SCHOOL AGE CHILDREN - Pambudi, Agung Setyo; Marni, Marni (Jurnal AKPER GSH, 2020)
Background: Food availability and safety are basic human rights. This problem is currently a world concern because hundreds of millions of people are reported to be suffering from diseases caused by food poisoning, one of the groups of people who often experience problems due to poisoning of street food is the elementary school (SD) student group because of their low knowledge of food safety. Snacks for school children are a problem that needs to be paid attention to by the community, especially parents and teachers because this snack food is very risky for biological or chemical contamination which disturbs health, both short and long term. In developing countries, up to about 70% of cases of diarrheal disease are related to consumption of contaminated food. Purpose of Writing: To determine the effect of health education on healthy snacks on children's attitudes in choosing healthy snacks for primary school aged children. Methods: This study uses a case study method (Case Study). Participants were 3 elementary school aged children. The instruments used were leaflets and stationery. Results: Subjects experienced increased knowledge about healthy food and healthy snacks. Conclusion: Health education is proven to be able to overcome the lack of knowledge in elementary school age children